2021
DOI: 10.3390/polym13162754
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Polycaprolactone in Three-Dimensional Printing Scaffolds for Bone Tissue Engineering

Abstract: Bone tissue engineering commonly encompasses the use of three-dimensional (3D) scaffolds to provide a suitable microenvironment for the propagation of cells to regenerate damaged tissues or organs. 3D printing technology has been extensively applied to allow direct 3D scaffolds manufacturing. Polycaprolactone (PCL) has been widely used in the fabrication of 3D scaffolds in the field of bone tissue engineering due to its advantages such as good biocompatibility, slow degradation rate, the less acidic breakdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 136 publications
2
67
0
Order By: Relevance
“…Our 3D printing approach has notable advantages over conventional drug delivery systems, such as customized and flexible drug design capabilities in choosing the desired dose, shape, and size for patient needs [ 10 ]. Polycaprolactone (PCL) is one of the most common materials used in fabricating scaffolds for tissue regeneration [ 11 ]. This polymer is a Food and Drug Administration (FDA)-approved linear polyester with good biocompatibility, slow degradation rate, fewer acidic breakdown products in comparison to other polyesters, and the potential for loadbearing applications [ 12 , 13 ]; in addition, it has a low melting point (59–64 °C) and exceptional blend compatibility with other synthetic polymers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our 3D printing approach has notable advantages over conventional drug delivery systems, such as customized and flexible drug design capabilities in choosing the desired dose, shape, and size for patient needs [ 10 ]. Polycaprolactone (PCL) is one of the most common materials used in fabricating scaffolds for tissue regeneration [ 11 ]. This polymer is a Food and Drug Administration (FDA)-approved linear polyester with good biocompatibility, slow degradation rate, fewer acidic breakdown products in comparison to other polyesters, and the potential for loadbearing applications [ 12 , 13 ]; in addition, it has a low melting point (59–64 °C) and exceptional blend compatibility with other synthetic polymers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although pure polyesters are biodegradable and bioresorbable, without modifications they do not possess enough rigidity for resistance during implant insertion, and the degradative products can cause inflammatory reactions, so they cannot be used for orthopedic applications. These limitations of thermoplastic polyesters can be overcome by introducing bioactive ceramics such as HA, tricalcium phosphate (TCP), and bioactive glass (BG) [ 52 , 53 , 54 ]. The literature revealed that polyesters mixed with HA [ 55 , 56 ], PLA, and PGA mixed with BG [ 57 , 58 ] have been extensively studied as materials for orthopedic applications in terms of their processing, physicochemical, mechanical, and in vitro biological properties.…”
Section: Orthopedic Applicationsmentioning
confidence: 99%
“…The micro injection molding process can prepare large-scale devices for cell proliferation and differentiation ( Matschuk et al, 2010 ). Micro-injection has also shown great potential in the field of bone tissue engineering, to cooperate with new materials and achieve comprehensive biological and mechanical properties ( Chen et al, 2017 ; Yang X. et al, 2021 ). Cai et al ( Cai et al, 2021 ) prepared PLGA/PCL fixation plate by in-situ fibrillation in micro-injection process ( Figure 6D ).…”
Section: Micro Injection Moldingmentioning
confidence: 99%